ANALYSIS OF THE VITREORETINAL SURGICAL FELLOWSHIP APPLICANT POOL: Publication Misrepresentations and Predictors of Future Academic Output. Issue 10 (October 2020) - Yannuzzi, Nicolas A.; Smith, Logan; Yadegari, Dan; Venincasa, Michael J.; Al-Khersan, Hasenin; Patel, Nimesh A.; Albini, Thomas; Berrocal, Audina M.; Flynn, Harry W.; Sridhar, Jayanth
Abstract : Purpose: To evaluate characteristics associated with misrepresentation of publication record, future career placement, and subsequent academic output among vitreoretinal surgical fellowship applicants. Methods: A retrospective review of 337 vitreoretinal surgical applicants between 2015 and 2018 was conducted. Publications reported in the applications were verified using PubMed, Google, and Google Scholar. Applications were considered misrepresented if there was no record of the publication or if there was an inconsistency in authorship. Applicants were followed after graduation and their employment position and postgraduation publications were recorded. The main outcome measures were the number of unverifiable publications, postfellowship job placement, and postgraduate peer-reviewed publications. Results: Of the 377 applicants, 309 (82.0%) listed peer-reviewed publications. Of those with a publication, 32 (10.4%) had misrepresentations. A reported desire to pursue an academic career was associated with a future career in academic medicine, whereas Alpha Omega Alpha status was correlated with a future career in private practice. Alpha Omega Alpha status, a reported desire to pursue an academic career, and the number of peer-reviewed publications before fellowship were positively correlated with higher numbers of peer-reviewed publications after fellowship. Conclusion: Unverifiable authorship among vitreoretinal surgical fellowship applicants is significant, affecting nearly one in 10 applicants with peer-reviewed publications. A reported desire to pursue academic medicine as listed on the fellowship application is a useful indicator for a future career in academics, and for increased number of peer-reviewed publications after fellowship. Abstract : Unverifiable authorship among vitreoretinal surgical fellowship applicants is significant. A number of demographic factors may be predictive of a future career in academic medicine after fellowship graduation.